Antimalarial myopathy: an underdiagnosed complication? Prospective longitudinal study of 119 patients. Issue 3 (11th August 2005) - Casado, E; Gratacós, J; Tolosa, C; Martínez, J M; Ojanguren, I; Ariza, A; Real, J; Sanjuán, A; Larrosa, M
Abstract : Objectives: To evaluate the prevalence and incidence of antimalarial myopathy in patients with rheumatic diseases treated with antimalarial drugs. Methods: Over a three year period, all patients with rheumatic diseases who were taking antimalarial drugs were studied. Serum muscle enzymes were assessed at the time of inclusion and every six months thereafter. Muscle strength, electromyography (EMG), and muscle biopsy were assessed in patients with a persistent muscle enzyme disturbances. Results: 119 patients were included (111 chloroquine, eight hydroxychloroquine). Of these, 22 (18.5%) had a persistent muscle enzyme disturbance: lactate dehydrogenase 19/22 (86%); creatine kinase 7/22 (32%), and aldolase 3/22 (14%). Findings of antimalarial myopathy were detected in 3/15 biopsied patients (20%) by light microscopy and in all 15 by electron microscopy. Eleven patients had myopathy at the time of inclusion (prevalence 9.2%) and four patients developed muscle injury during follow up (annual incidence 1.2%). Muscle weakness was observed in 8 of 15 patients with biopsy proven myopathy, giving a prevalence of clinical antimalarial myopathy of 6.7%. All these patients also had a myopathic pattern on electromyography. Conclusions: The prevalence of antimalarial myopathy is higher than previously recognised when muscle enzyme determination is used as a screening method. When a persistent muscle enzyme disturbance is observed, clinical and electromyographic studies should be undertaken periodically to detect the development of clinical myopathy. In cases of clinical myopathy, an anatomical-pathological tissue study, including an ultrastructural study, is mandatory to confirm the diagnosis.